COLLABORATIVE LEARNING: BOOSTING QAWAID MASTERY WITH STAD MODEL - Muhammad Jundi; Laily Fitriani; Anhar Aquil (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
AbstractThis research aims to investigate the use of the Student Teams Achievement Divisions (STAD) Cooperative Learning Model in enhancing collaboration among students in the Arabic qawaid material. The study examines the technical implementation steps of STAD and evaluates its impact on students' awareness of collaboration. A qualitative research approach with a case study design was employed. The participants consisted of students engaged in the implementation of STAD. Data were collected through classroom observations, interviews, and document analysis. The findings revealed that the technical implementation steps of STAD significantly contribute to improving collaboration among students. The students exhibited increased awareness of the importance of collaboration in achieving common academic goals. However, it was also found that enhancing collaboration requires consistent time and effort. This research holds important implications for the development of cooperative learning in the educational environment and provides recommendations for teachers and educational practitioners to effectively implement STAD and enhance collaboration among students. AbstrakPenelitian ini bertujuan untuk menginvestigasi penggunaan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions (STAD) dalam meningkatkan kerja sama antara siswa di materi qawaid bahasa Arab. Penelitian dilakukan dengan memperhatikan langkah-langkah teknis implementasi STAD dan mengevaluasi dampaknya terhadap kesadaran siswa tentang kerja sama. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan studi kasus. Partisipan penelitian terdiri dari siswa kelas yang terlibat dalam implementasi STAD. Data dikumpulkan melalui observasi kelas, wawancara, dan analisis dokumen. Hasil penelitian menunjukkan bahwa langkah-langkah teknis implementasi STAD dapat memberikan kontribusi signifikan dalam meningkatkan kerja sama di antara siswa. Para siswa mengalami peningkatan kesadaran tentang pentingnya kerja sama dalam mencapai tujuan akademik yang sama. Namun, ditemukan pula bahwa peningkatan kerja sama membutuhkan waktu dan upaya yang konsisten. Penelitian ini memiliki implikasi penting dalam pengembangan pembelajaran kooperatif di lingkungan pendidikan dan memberikan rekomendasi bagi guru dan praktisi pendidikan dalam menerapkan STAD secara efektif untuk meningkatkan kerja sama di antara siswa.